Comparison between the Effect of multi-walled carbon nanotubes and single walled carbon nanotubes in removing pb and cd in contaminated bio medical ash - Kanoosh, Abbas A; Alabdraba, Waleed M Sh; Al-Obaidi, Ahmed (Edelweiss Applied Science and Technology, 2024)
Heavy metal contamination is a highly significant environmental issue. Primarily, this current study is focusing the application of developing Nano technologies which have capacity to remove or reduce toxins from the environment. The extraction and preconcentration abilities of both types of carbon nanotubes, multi-walled (MWCNTs) and single-walled (SWCNTs), were accomplished by using water-acid, acetate, and deghassed water acid EDTA solutions from neuteuche semi-total solid extract from anthropogenic and naturally in origine samples. The results of the study indicated that the adsorption rate was even faster when the solution temperatures were higher in both types of adsorbents. These increases were greater when multi-walled carbon was used. This may be due to the fact that in endothermic nature of adsorption the increase in temperature leads to a faster rate of adsorption. In order to understand the kinetics of Cadmium (II) and Lead(II) adsorption, analysis was executed utilizing the fractional power function model and Lagergren pseudo-first-order and pseudo-second-order methods. A pseudo-second-order model well described the adsorption kinetics of heavy metal ions onto both bioadsorbents. For both biosorbents, the adsorption capacity increased as the solution was heated. The percentage of Pb adsorbed on ultra-sonically assisted MWCNTs was 7.93%, for MWCNTs= 8.33%, 73.50% for swCNTs and 92.46% for amine-MWCNTs (Table 2). Similarly, the percentage of Cd adsorbed on ultra-sonically assisted MWCNTs was 67.92%, 29.30% for MWCNTs, 6.30% for swCNTs and 2.27% for amine-MWCNTs. As far as SWCNTs, they provided some interesting results in terms of adsorption capacity. For example, the adsorption capacity with respect to Pb was about 6.53% with SWCNTs 1, about 7.12% with SWCNTs 2, about 61.33% with SWCNTs 3, and about 79.31% with SWCNTs 4. Similarly, for Cd it was about 61.32% with SWCNTs 1, about 27.13% with SWCNTs 2, about 5.88% with SWCNTs 3, and about 1.53% with SWCNTs 4. The elution tests for single-walled carbon nanotubes and multiwalled carbon nanotubes have been carried out and the results have been shown as binding isotherms and pH effects in Figures 3 and 4. For the study of the adsorption capability of single-walled carbon nanotubes for metal ions, same order of binding to the metal ions has been observed for both the types of the carbon nanotubes-studied, lead (II) < cadmium (II). For multi-walled carbon nanotubes, however, the binding of metal ions was found to depend on the carbon nanotubes type and the binding order, as for carbon nanotubes, were found to be, lead (II) > cadmium (II). Nanotechnologies have facilitated the ability of researchers to address challenges more effectively. This research focuses on the development of Nanotechnologies for the purpose of remediating heavy metals, including cadmium and lead. These metals are considered highly toxic and require urgent attention.